Effects of four drying methods on Amomum villosum Lour. 'Guiyan1' volatile organic compounds analyzed via headspace solid phase microextraction and gas chromatography-mass spectrometry coupled with OPLS-DA. Issue 41 (16th September 2022) - Tu, Xinghao; Liu, Yijun; Yanli, Yao; Wenxiu, Li; Ping, Luo; Du, Liqing; He, Junjun; Jian-neng, Lu
Abstract : This paper analyzed the effects of four drying methods (heat pump drying, hot air drying, sun drying, and freeze drying) on the volatile organic compounds (VOCs) in fresh 'Guiyan1' Amomum villosum Lour. Abstract : This paper analyzed the effects of four drying methods (heat pump drying, hot air drying, sun drying, and freeze drying) on the volatile organic compounds (VOCs) in fresh 'Guiyan1' Amomum villosum Lour. Via separation, component differentiation, and overall variance analysis via HS-SPME-GC/MS coupled with OPLS-DA, 133 kinds of VOCs, mainly composed of hydrocarbons, esters, and alcohols, were identified. The differences in 'Guiyan1' processed by freeze-drying and the other three drying methods were the most significant and easily distinguishable. The main VOCs in the dried samples were bornyl acetate and 2-bornanone, with the largest increase in 2-bornanone and the largest decrease in bicyclogermacrene. The obtained data provided guidance for optimizing the processing and storage of 'Guiyan1'.